Pengaruh Penerapan Program E-Samsat dan Kualitas Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kantor Samsat Kabupaten Bandung II Soreang - Nisa, Khaerun; Saepuloh, Cepi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
By utilizing technological advances, the Indonesian government has developed innovative online-based Samsat services, namely E-Samsat (Electronic One-Stop Single Administration System). This program was launched to increase taxpayer compliance and make it easier to pay motor vehicle tax without having to come directly to the Samsat office. This research aims to determine the effect of implementing the E-Samsat program and the quality of tax services on motor vehicle taxpayer compliance at the Bandung II Soreang Regency Samsat Office. This research uses a quantitative approach. The data obtained by this research, apart from secondary data, also includes primary data, namely distributing questionnaires to 100 registered motor vehicle taxpayers in Bandung Regency. The results of this research show that the implementation of the E-Samsat program and the quality of tax services each have a positive and significant influence on motor vehicle taxpayer compliance. This research also shows that the government needs to increase socialization and education regarding E-Samsat to increase its adoption. In this way, the digital-based tax system can be further optimized.